Analysis of the Use of TikTok Application on the Language Politeness of Elementary School Students (Current Research in Education: Conference Series Journal, 2024)
The latest interesting innovation created by technology creators to be able to compete is Tiktok social media. This study aims to analyze the impact of using the TikTok application on student language politeness, the method used in this research is qualitative with a case study approach. The data collection techniques in this study were observation, interviews, and documentation. The subject of this research is fifth grade students of SDN Anggadita I. The results of the study state that the unwise use of the TikTok application causes students' language politeness to decline, students often use impolite language when interacting with peers and teachers, and students always follow trends that emerge without giving restrictions. Lack of attention and supervision from parents is one of the factors that make it easy for students to follow the impolite language they hear in the TikTok application. In addition, parents at home also give freedom to children in social media.